LANGUAGE 1 MORPHOLOGICAL INTERFERENCE ON LANGUAGE 2 ACQUISITION IN UZBEK LEARNERS - Kubayev Mansur Abdumo`min o`g`li; Amanova Madina Xamid qizi (Journal of new century innovations, 2024)
Abstract: No matter English is being taught to Uzbek students from an early age, the majority of Uzbek people are still thriving on acquiring the language. They find it quite complicated to acquire the language especially up to the level of communicative competence. Wong-Fillmore in Jay (2003) points out that learning a second language demands learning large chunks of speech which are used communication purposes; however, SLA has several hindrances for learners to face. Even though learners complete a course, they still make mistakes and have never been able to acquire language as any native does, so inter-language is inevitable.